1992
DOI: 10.1159/000173457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods for Estimating Renal Medullary Blood Flow

Abstract: Although only 10-15% of renal blood flow enters the medulla, renal medullary hemodynamics have been implicated as a key factor for the ability of the kidney to excrete concentrated or diluted urine and to be involved in sodium homeostasis. Due to the obvious importance of medullary hemodynamics, several methods have been developed or modified for estimating regional renal blood flow. The aim of the present paper is to evaluate critically the most commonly used methods available today. Those which are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…These studies suggested variously that MBF is more sensitive than CBF to neural activation (12) or that renal nerve stimulation can increase MBF (24). Regardless, these studies should be interpreted with great care, because the validity of their methodology has been questioned (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested variously that MBF is more sensitive than CBF to neural activation (12) or that renal nerve stimulation can increase MBF (24). Regardless, these studies should be interpreted with great care, because the validity of their methodology has been questioned (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…Renal medullary blood flow is normally low in order to preserve osmotic gradients and enhance urinary concentration [12,13]. At the same time, medullary oxygen consumption is high, since the medullary thick ascending limb is responsible for the generation of an osmotic gradient by active reabsorption of sodium.…”
mentioning
confidence: 99%
“…lc). The variability in flow measurements was within expected ranges, as described previously [9,20,321. The calculated vascular resistances did not indicate a decreasing vascular tone in macrovasculature or micro-vasculature (Table 1) tective effect of ET-A receptor blockade to its known anti-proliferative properties or to a concomitant improvement of renal hemodynamics.…”
Section: Resultsmentioning
confidence: 60%
“…The signals of the two probes were transmitted to a laser flow meter (MBF 3D, Moor Instruments). Validation of transit time and laser Doppler methods are given elsewhere [17,20,321. The experimental setting was established and has been used in several projects in our laboratory.…”
Section: Hemodynamic Studiesmentioning
confidence: 99%